Out of place re-claiming the self in Kate Chopin's The Awakening and Latifa Al-Zayyat's The Open Door - Abbas, Mai Mohammad (AUC Knowledge Fountain, 2011)
This thesis aims at exploring the self-imposed marginalization as well as the reshaping of the self of two unique female figures in literature while discussing the nature, the reasons and the impact of their attitude. The two characters who are studied in their out of place experience are Edna Pontellier, a nineteenth-century American in Kate Chopin's The Awakening and Layla Sulayman from twentieth-century Egypt in Latifa Al-Zayyat's The Open Door. The two characters are not chosen randomly, for, although they live in different times and places, they share a similar dilemma. Both are driven by their coercive families to struggle against those traditions which continuously dictate a strict and limited life while molding them into pawns, void of personality and critical thinking. As a result, both heroines resort to a fictitious world which â promisesâ protection from the frustrations and liberation of the restrictions of real life. Each character dissolves in her own way within this fictitious world. Eventually both Edna and Layla need to make a choice: either lurk forever in their imaginary world or face reality and responsibility. While each heroine takes her own decision, they both attempt to claim a radically new and free â selfâ .